(3GdaJGhi GdeajOI hGdCLhHI GdSOjOIs - (3Ydj Hf YHO GdcGaj Hf Ydj Hf JeGe GdSHcj GdCfUGQj GdNRQLj, CHh GdMSf, Jbqj GdOjf,J (B756 (3g` s
(3ChdgG (B:s
(3SFd GdTjN GdEeGe GdYGde GdSHci eG Jbhd GdSGOI GdabgGA CFeg GdOjf QVi Gddg Yfge CLeYjf ai QLd MHjS CeGcf hLYd GdfXQ ajgG ef HYOg dCHfJg dUdHg s
(3BNQgG (B:s
(3JfJgi HeSFdI hQOJ Ydi GdTjN ef OejGW SfI (B732 s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B302s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdQjGVjGJs